Strategi Bimbingan Dan Konseling Dalam Mendukung Wanita Berkarir: Menyeimbangkan Kehidupan Pribadi Dan Profesional - Nadhira, Alifia Hasya; Puspa, Ghea Amanda Cahaya (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Currently, women play dual roles as homemakers and professionals and are challenged to balance their personal lives and careers. This research aims to understand the importance of counseling services in supporting career women to balance their personal and professional lives. The research method used is a literature review, analyzing articles obtained from the Google Scholar database. The findings indicate that counselors can provide significant assistance through feminist counseling. Feminist counseling services help career women build confidence in their ability to achieve work-life balance.